Comparison of serum soluble edoglin (sEng) level in eary onset preeclampsia, late onset preeclampsia and normal pregnant woman - Aldika Akbar; Mita Herdiyantini; Aditiawarman Aditiawarman (Universitas Airlangga, 2017)
Objectives: This study aimed to compare the serum levels of soluble Endoglin (s-Eng) between early onset preeclampsia, late onset preeclampsia and normal pregnant women.Materials and Methods: This was an analytic observational study (Cross-Sectional) performed on 39 pregnant women with early-onset preeclampsia (EO-PE), late-onset preeclampsia (LO-PE), and normal pregnancy. The patients were consecutively chosen in Dr. Soetomo Hospital, Airlangga University Hospital and Dr. M. Soewandhi Hospital Surabaya in May-July 2016. The serum concentration of soluble Endoglin were collected by venous puncture taken from maternal circulation and measured by ELISA.Results: From this study, serum concentrations of soluble Endoglin was higher significantly on the early onset preeclampsia compared with late onset preeclampsia and normal pregnancy (47,65 ± 40,17 vs 13,46 ± 9,48 vs 6,11 ± 1,45 ng/mL; p=0.000). Conclusion: This study shows angiogenic imbalance was more prominent compared in early-onset than late-onset preeclampsia. This may be because the placental dysfunction, placental ischemia, which produce excessive anti angiogenic factors, whic later causing endothelial dysfunction was more related to early onset preeclampsia.